APPLICATION OF NEW IMPROVED SOLUTIONS OF PREPARATIONS BASED ON ZEOLITH IN DIFFERENT PHASES OF PRODUCTION AT THE GRAPEVINE IN THE REPUBLIC OF NORTH MACEDONIA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
In the period from 2018 to 2023, we conducted research on the effects of the application of the innovative formula from the mineral zeolite on different stages of production in the grapevine in the Republic of North Macedonia. The mineral zeolite originates from the mine excavations in Serbia. In the period from 2017 to 2018, a „improved formula‟ was made from the zeolite preparation with processing, it was crushed into a powder form, with a certain particle size for easy application in a dissolved state. This type of processed zeolite is registered as a soil improver and during that period it received an innovation award at a fair in Romania. We, in our country, continuously carry out tests using this preparation in several crops and it always gave positive results. In our study, the physico-chemical properties of this type of zeolite are shown, and then the results and the effect of the application on the vines are shown. The main goal of applying this „ improved zeolite formula‟ was to reduce the use and uncontrolled use of pesticides in the fight to suppress diseases, pests, harmful weeds, etc. This is achieved in such a way that with the application of zeolite, which is environmentally friendly, the properties of the soil are improved, the plant makes better use of useful substances and water, in fact stronger, more resistant and immune plants to diseases, pests, harmful weeds, drought, frost are obtained. etc. At the same time, the use of pesticides is reduced, and the pollution of the environment is also reduced.